PERENCANAAN PAJAK UNTUK EFISIENSI PEMBAYARAN PAJAK PADA PT KALTIM LESTARI UNGGUL - -, Andi Kantono (EKONOMIA, 2014)
The purpose of this study was to determine the calculation of income tax PT. Kaltim Lestari Unggul before and after applicable tax planning to improve the efficiency of the payment of tax burden. The analysis tools being used was Number of tax laws. 36 of 2008, Fiscal correction of the costs included in Law No. taxation. 36 of 2008, Calculating and tax planning on taxpayer income tax in 2012, comparing taxable income before and after tax planning. Based on the results of a study of the incomeÂ  statement of PT. Kaltim Lestari Unggul, it had been found that payment of income tax expense using the right tax planning in accordance with the provisions of the tax laws No.. 36 of 2008 in PT Kaltim Lestari Unggul in 2012 to minimize the burden of the tax to be paid.